Analysis of Aftershock Earthquake Decay in Mamberamo on September 10, 2022 using GEOSTAT V2.0 Software - Takhul Bakhtiar; Muh Nahdhi Ahsan; Armansyah Armansyah; Danang Pamuji Dwi Lestari Yanto (PRISMA FISIKA, 2022)
There was an earthquake on September 10, 2022 with a magnitude of 6.2 with a depth of 16 km in Mamberamo Raya, Papua. This earthquake is located at coordinates 2.04 ° South Latitude - 138.26 ° East Longitude. This earthquake produced 93 aftershocks since seven days after the mainshock. This study aims to determine the end time of aftershock decay. This study uses the Mogi I, Mogi II, Utsu and Omori methods contained in the GEOSTAT V2.0 software. The approach of observational data in real time is carried out to validate the selected calculation method. This aftershock decay analysis aims to mitigate earthquake disasters to the public in the form of information on the estimated decay time of aftershocks. The calculation of the Mogi I method shows that the aftershock experienced a decay on the 9th day of September 18, 2022 (r = -0.94157). The calculation of the Mogi II method shows that the aftershock experienced a decay on the 7th day of September 17, 2022 (r = -089415). While the calculation of the Omori method shows that the aftershock earthquake experienced decay on the 6th day of September 16, 2022 (r = 081628) and the calculation method of the Utsu method showed that the aftershock experienced decay on the 9th day of September 18 2022 (r = -094154). The calculation method that is close to BMKG real time observation is the Utsu method with a decay time on the 9th day of September 18, 2022 (r = -0.94154).